A framework for the optimal sizing of hybrid solar pv-battery-hydro system for a rural house in malaysia - Bhayo, B.A. (Springer Science and Business Media Deutschland GmbH, 2020)
This paper presents a framework for the optimal sizing of hybrid system utilizing the solar energy and direct rainfall for power generation to meet the load demand of rural house in Malaysia. The rainfall through catchment area is utilized to generate power when the power from PV is not enough to meet the load demand. The loss of power supply probability (LPSP) is considered as constant value for four different case studies. Case 1 and Case 2 are the PV-Battery system and PV-Battery-Hydro system, respectively, with LPSP of 0.0. Case 3 and Case 4 are the PV-Battery system and PV-Battery-Hydro system, respectively, with LPSP of 0.02. Using particle swarm optimization (PSO), the optimal sizing is determined based on the minimization of levelized cost of energy (LCE). For LPSP of 0.0, the integration of only 0.05 kWh rainfall-based hydropower systems with PV-Battery system resulted in reduction in the battery capacity of about 2.66. Compared to other cases, the lowest LCE of about 0.3613 /kWh is found for Case 3. For the LPSP of 0.0, the power systems are oversized, which resulted in high LCE. The integration of rainfall-based hydropower system with PV-Battery system for LPSP of 0.0 and 0.02 has increased and decreased the surplus power by 0.8 and 2.5, respectively, than the conventional PV-Battery system. It is intimated that with robust power management and water storage, the integrated solar/rainfall-based hydro system can be of more advantageous. Â© Springer Nature Singapore Pte Ltd 2020.